Testes de capacidade funcional utilizados para avaliar crianças com cardiopatia congênita: Uma revisão sistemática - Alves, Cíntia Santos (2021)
Introduction: Congenital heart diseases account for almost a third of all major congenital anomalies. Individuals with these conditions have an impaired exercise response, but few studies have assessed the functional capacity of the pediatric population with this condition. There are several tests to assess functional capacity, but none are specific for children with congenital heart disease. Objective: This review aims to analyze the functional capacity tests used in children with congenital heart disease. Material and methods: A systematic review was carried out in accordance with PRISMA guidelines and registered with PROSPERO. The quality of the studies was assessed using the Newcastle-Ottawa and ROBINS-I scale. Results: 14 studies were included in this review, 13 observational studies and 1 non-randomized study. The tests found were: 11 TECP (79%); 1 TC6M (7%); 2 Exercise test (14%). No studies were found that assessed psychometric properties, diagnostic accuracy or that validated these tests for children with CHD. No study presented low risk of bias studies and 4 studies presented high risk of bias studies. Conclusion: Studies that assess the physical status of children with CHD have mostly opted for CPET. Field tests are rarely used to assess this population. No studies were found to validate these tests in children with CHD.